Why women do not ask for information on preconception health? A qualitative study. Issue 1 (December 2017) - Bortolus, Renata; Oprandi, Nadia; Rech Morassutti, Francesca; Marchetto, Luca; Filippini, Francesca; Agricola, Eleonora; Tozzi, Alberto; Castellani, Carlo; Lalatta, Faustina; Rusticali, Bruno; Mastroiacovo, Pierpaolo
Abstract Background Preconception care involves health promotion to reduce risk factors that might affect women and couples of childbearing age. The risk factors of adverse reproductive outcomes include recognized genetic diseases in the family or the individual, previous congenital diseases, miscarriage, prematurity, fetal growth restriction, infertility, chronic maternal diseases, lifestyle, and occupational or environmental factors. Effective preconception care involves a range of preventive, therapeutic and behavioural interventions. Although in Italy there are national preconception care recommendations concerning the general population, they are usually encouraged informally and only for single risk factors. At present there is increasing interest in offering a global intervention in this field. The aim of this study was to investigate attitudes and behaviours of Italian women of childbearing age and healthcare professionals regarding preconception health. Methods We conducted a qualitative study among women of childbearing age and healthcare professionals between February 2014 and February 2015. Five focus groups were held: 2 with non-pregnant women aged 22 to 44 years and 3 with healthcare professionals. Discussion topics included women's questions about preconception health, worries and barriers regarding preconception care interventions, attitudes and behaviours of women and healthcare professionals towards preconception health, women's information sources. In the analysis of the focus groups priority was given to what was said by the women, supplemented by information from the healthcare professionals' focus groups. Results Fourteen women of childbearing age (8 nulliparae and 6 multiparae) and 12 healthcare professionals (3 nurses, 4 midwives, 5 doctors) participated in the focus groups. The results indicate the presence of many barriers and a lack of awareness of preconception health relating to women, healthcare professionals and policies. Women's knowledge and attitudes towards primary preconception care information are described. The main reference source of information in this field for Italian women seems to be their obstetric-gynaecologist. Conclusions The study indicates that several barriers influence preconception care in Italy. Moreover, a lack of awareness of preconception health and care among Italian women of childbearing age and healthcare professionals emerges. The findings might contribute to strategies for the implementation of preconception care guidelines.